Advanced Techniques for Endoscopic Intracerebral Hemorrhage Evacuation: A Technical Report With Case Examples. Issue 1 (22nd April 2020) - Rothrock, Robert J; Chartrain, Alexander G; Scaggiante, Jacopo; Pan, Jonathan; Song, Rui; Hom, Danny; Lieber, Adam C; Bederson, Joshua B; Mocco, J; Kellner, Christopher P
Abstract: BACKGROUND: Multiple surgical techniques to perform minimally invasive intracerebral hemorrhage (ICH) evacuation are currently under investigation. The use of an adjunctive aspiration device permits controlled suction through an endoscope, minimizing collateral damage from the access tract. As with increased experience with any new procedure, performance of endoscopic minimally invasive ICH evacuation requires development of a unique set of operative tenets and techniques. OBJECTIVE: To describe operative nuances of endoscopic minimally invasive ICH evacuation developed at a single center over an experience of 80 procedures. METHODS: Endoscopic minimally invasive ICH evacuation was performed on 79 consecutive eligible patients who presented a single Health System between March 2016 and May 2018. We summarize 4 core operative tenets and 4 main techniques used in 80 procedures. RESULTS: A total of 80 endoscopic minimally invasive ICH evacuations were performed utilizing the described surgical techniques. The average preoperative and postoperative volumes were 49.5 mL (standard deviation [SD] 31.1 mL, interquartile range [IQR] 30.2) and 5.4 mL (SD 9.6, mL IQR 5.1), respectively, with an average evacuation rate of 88.7%. All cause 30-d mortality was 8.9%. CONCLUSION: As experience builds with endoscopic minimally invasive ICH evacuation, academic discussion of specific surgical techniques will be critical to maximizing its safety and efficacy.